O uso do Cinábrio em alguns monumentos megalíticos funerários do Alentejo (Portugal). The use of cinnabar in some funerary megalithic monuments of the Alentejo (Portugal)/El uso de cinabrio en algunos monumentos megalíticos funerarios en Alentejo (Portugal) - Rocha, Leonor (2021)
In the Iberian peninsula, and in particular in the Alentejo´s region, there are a large number of Megalithic monuments, both funerary and non-funerary. The vast majority of these monuments were excavated in the beginning of the 20th century, in most cases without using proper methodologies. These archaeological excavations yielded a large number of artefacts without proper archaeological context, which are nowadays stored in the Portuguese national museums. During the last years, a systematic approach has been undertaken to study some exotic materials exhumed in some of those megalithic monuments. Using SEM-EDX, Raman spectroscopy and micro-XRD we were able to identify the chemical composition of the red pigments recovered in a selection of megalithic monuments form Alentejo. Cinnabar and ochre were identified alone or mixed in several monuments, but it is unknown if that mixture was done intentionally or not.This study demonstrates the need to use the appropriate analytical methodology in order to properly identify the nature of red pigments found in archaeological context.